Policy Evaluation Of Post-2013 Curriculum in Madrasah Ibtidaiyah - Aswaruddin Aswaruddin; Syafaruddin Syafaruddin (STAI Miftahul Ula Nganjuk, 2021)
The purpose of this research is to find out the implementation of curriculum policy in madrasah Ibtidaiyah Negeri 4 Kota Medan, this research method is qualitative descriptive research method, data collection technique through interviews, observations (observations), and documentation and triangulation with tools in the form of interview guidelines, and obervasi guidelines. Determination of research subjects (informants) using purposive techniques or aimed samples consisting of madrassa heads and teachers. The results of this research are the Implementation of Curriculum Policy 2013 in Madrasah Ibtidaiyah Negeri 4 Medan City has at least brought changes including, students can be more productive, creative, innovative and effective. In addition, students can also be passionate and happy in madrasah, from the aspect of educators and education personnel with this change, they can be more passionate in teaching and easier in meeting the provisions of 24 hours of teaching per week, from the aspect of management of educational units. Communication and resource factors are contributing factors to implementing the 2013 curriculum policy. So that the implementation of the 2013 Curriculum is expected to improve the reputation of madrasas on the one hand and the reputation of the country on the other. Then, the implementation of the 2013 curriculum policy in Madrasah Ibtidaiyah Negeri 4 Medan City can increase competitiveness and development of the nation's civilization.